Periodic optimal control of nonlinear constrained systems using economic model predictive control. (August 2020) - Köhler, Johannes; Müller, Matthias A.; Allgöwer, Frank
Abstract: In this paper, we consider the problem of periodic optimal control of nonlinear systems subject to online changing and periodically time-varying economic performance measures using model predictive control (MPC). The proposed economic MPC scheme uses an online optimized artificial periodic orbit to ensure recursive feasibility and constraint satisfaction despite unpredictable changes in the economic performance index. We demonstrate that the direct extension of existing methods to periodic orbits does not necessarily yield the desirable closed-loop economic performance. Instead, we carefully revise the constraints on the artificial trajectory, which ensures that the closed-loop average performance is no worse than a locally optimal periodic orbit. In the special case that the prediction horizon is set to zero, the proposed scheme is a modified version of recent publications using periodicity constraints, with the important difference that the resulting closed loop has more degrees of freedom which are vital to ensure convergence to an optimal periodic orbit. In addition, we detail a tailored offline computation of suitable terminal ingredients, which are both theoretically and practically beneficial for closed-loop performance improvement. Finally, we demonstrate the practicality and performance improvements of the proposed approach on benchmark examples. Highlights: We provide a novel MPC design with guaranteed economic performance for dynamic/periodic nonlinear constrained problems. Naive/Alternative formulations for dynamic/periodic case do not yield desirable performance guarantees. A novel design procedure for terminal ingredients for economic dynamic operation is presented. We demonstrate performance benefits for a periodic time-varying HVAC system and a time-invariant nonlinear CSTR system.